More than Just a Photo? Aura Photography in Digital Japan - Gaitanidis, Ioannis (2019)
The sudden disappearance from the market in 2016 of the type of polaroid film that happens to be used by cameras that are specially built to capture the halo of energy (or “aura”) believed to be surrounding human beings has made those cameras obsolete. As a result, Japanese aura camera owners who make a living from counseling clients based on a “reading” of aura photos express worry in regard to their loss of authority over the process of production of these photographs. At the same time, a historical analysis of aura photos as a sub-type of spirit photography shows that the popularization of specially built aura cameras had already led to the standardization of the “reading” of aura photos that is more prominent today in digital smartphone versions of the original aura cameras. Technological and religious authorities intermingle in this case-study and influence each other, showing an example of (partial) desacralization of religious media, at the expense of religious experts endowed with the ability to use them.